Whole‐exome sequencing identifies a homozygous donor splice‐site mutation in STAG3 that causes primary ovarian insufficiency. Issue 2 (17th August 2017) - He, W.‐B.; Banerjee, S.; Meng, L.‐L.; Du, J.; Gong, F.; Huang, H.; Zhang, X.‐X.; Wang, Y.‐Y.; Lu, G.‐X.; Lin, G.; Tan, Y.‐Q.
Abstract : Primary ovarian insufficiency (POI) is the depletion or loss of normal ovarian function, which cause infertility in women before the age of 40 years. Two homozygous germline truncation mutations in STAG3 gene had been reported to causes POI in consanguineous families. Here, we aimed to identify the genetic cause of POI in 2 affected sisters manifested with primary amenorrhea and partial development of secondary sexual characters with normal range of height of a consanguineous Han Chinese family. Whole‐exome and Sanger sequencing identified a homozygous donor splice‐site mutation (NM_012447.2: c.1573+5G>A) in the STAG3 gene. RT‐PCR revealed that the mutation causes loss of wild‐type donor splice‐site which leads to aberrant splicing of STAG3 mRNA and consecutive formation of STAG3 alternative transcript (p.Leu490Thrfs*10) . This is the first report of splice‐site mutation of STAG3 gene causes POI in 2 Han Chinese patients. Abstract :